Transforming the Fashion MSMEs Industry through Social Media and Digital Technology Innovation - Ircham Suwarsang Putra; M Farid Wajdi; Muhammad Sholahuddin (JURNAL ILMIAH EDUNOMIKA, 2025)
The fashion industry, creative businesses, and social media have become important pillars in supporting the transformation of the creative economy in the digital era. This study explores how the integration of sustainability, digital technology, and social media-based strategies can boost the competitiveness of creative businesses in the fashion sector. The findings show that sustainability, through practices such as upcycling and community-based design, not only reduces environmental impact but also creates high social value. Digital technologies, including artificial intelligence (AI) and e-commerce, accelerate the design process, improve operational efficiency, and enable product personalization. Social media, such as Instagram and TikTok, play a key role in marketing and building long-term relationships with consumers. Cross-sector collaboration involving global technology and local culture has also been shown to strengthen innovation and support creative city branding. This study concludes that sustainability, technological innovation, and social media are key pillars of creative business transformation in the fashion sector. The integration of these three elements creates significant opportunities for business actors to adapt to market changes, increase global competitiveness, and support sustainable development goals